1989
DOI: 10.1159/000181286
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Improvement of Visual Defects with Parenteral Depot-Bromocriptine in a Patient with a Non-Functioning Pituitary Adenoma

Abstract: The management of non-functioning pituitary adenomas with bromocriptine is controversial, and surgical treatment is usually prescribed when the visual field is affected. Here we report, what we believe to be the first case of a patient with a non-functioning pituitary adenoma who experienced normalization of visual field defects and a substantial improvement in visual acuity after the parenteral administration of depot-bromocriptine. The patient’s tolerance to the drug was excellent. The results of the immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Reduction of the plasma hormone level by bromocriptine treatment was reported in a few patients with gonadotropinoma (5,(21)(22)(23). A few case reports have suggested that the occasional nonfunctioning pituitary tumor maydecrease in size in response to dopamine agonist treatment (24)(25)(26)(27)(28). Almost all of these tumors are likely to be gonadotropinomas, because the majority of clinically nonfunctioning pituitary adenomas are gonadotropinomas (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of the plasma hormone level by bromocriptine treatment was reported in a few patients with gonadotropinoma (5,(21)(22)(23). A few case reports have suggested that the occasional nonfunctioning pituitary tumor maydecrease in size in response to dopamine agonist treatment (24)(25)(26)(27)(28). Almost all of these tumors are likely to be gonadotropinomas, because the majority of clinically nonfunctioning pituitary adenomas are gonadotropinomas (3,4).…”
Section: Discussionmentioning
confidence: 99%